2013
DOI: 10.1007/s00795-013-0058-4
|View full text |Cite
|
Sign up to set email alerts
|

The expression of cytokeratin in keratocystic odontogenic tumor, orthokeratinized odontogenic cyst, dentigerous cyst, radicular cyst and dermoid cyst

Abstract: The epithelial lining of odontogenic keratocysts exhibits either parakeratosis or orthokeratosis. In 2005, the WHO classified odontogenic keratocysts with parakeratosis as keratocystic odontogenic tumors (KCOT). Odontogenic keratocysts with orthokeratosis were not classified as odontogenic tumors, but instead referred to as orthokeratinized odontogenic cysts (OOC). To clarify the difference between these two lesions, we investigated their biological characteristics using immunohistochemical studies for cytoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 15 publications
7
31
5
1
Order By: Relevance
“…CK13 (54 kDa) is present in the suprabasal layer of oral stratified squamous epithelium (23) and is expressed in odontogenic cysts and tumors (24)(25)(26). However, Tsuji et al (27) and Hayashi et al (28) reported that CK13 expression could not be confirmed in OOCs, being inconsistent with our present result. On the other hand, Koizumi (29) stated that CK13 was partially positive in OOCs, supporting of our result.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…CK13 (54 kDa) is present in the suprabasal layer of oral stratified squamous epithelium (23) and is expressed in odontogenic cysts and tumors (24)(25)(26). However, Tsuji et al (27) and Hayashi et al (28) reported that CK13 expression could not be confirmed in OOCs, being inconsistent with our present result. On the other hand, Koizumi (29) stated that CK13 was partially positive in OOCs, supporting of our result.…”
Section: Discussioncontrasting
confidence: 98%
“…In a comparison between OOCs as representative of developmental cysts and KCOTs as neoplastic cystic lesions, differences in expression were evident among CK10, CK17, and CK19. CK10 (56.5 kDa) is expressed in keratinized stratified squamous epithelium, except for the basal layer (25,27,29). CK10 positivity was evident in the Su and SP of OOCs, indicating they differ from lesions such as KCOTs and DCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a previous study showed that most OOCs and dermoid cyst specimens express CK10. This finding also suggests that OOCs may originate from the oral epithelial component, whereas KCOTs originate from dental lamina (13). This would explain the occurrence of KCOTs in the posterior mandible, where the dental lamina is more active at the age that patients develop this lesion (1).…”
Section: Discussionmentioning
confidence: 85%
“…They can lead to the formation of an inflammatory radicular-necrotic cyst (RC), that can be periapical or peri-radicular. First event is the formation of a granuloma, that subsequently gives rise to a cyst, whose epithelium expresses a specific odontogenic CK such as 19 in the superficial cell layers (24)(25)(26) and co-expresses CK5 in the cyst lining (18). A peculiar variant of RC is considered the Residual Radicular Cysts that develop from apical granulomas or residual fragments of RC (5,6).…”
Section: Cysts and Pseudocysts Of Oral Bone Tissue And Periodontalmentioning
confidence: 99%